1996
DOI: 10.1016/0370-2693(96)00722-8
|View full text |Cite
|
Sign up to set email alerts
|

Production of non-linear SUSY Higgs bosons at e+e− colliders

Abstract: We investigate the Higgs sector of a nonlinear supersymmetric standard model at LEP 1 and LEP 2, as well as at future linear e + e − colliders with √ s = 500, 1000, and 2000 GeV. The LEP 1 data do not put any constraints on the parameters of the model, and allow a massless Higgs boson in particular. For LEP 2, there are remarkable differences between the Higgs productions at √ s = 175 GeV on the one hand and that at √ s = 192 GeV and 205 GeV on the other hand. The case for √ s = 175 GeV is similar to LEP 1, wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…3. Clearly, even very light CP-even scalars are not ruled out if ξ 1 is sufficiently small, and such scenarios can indeed be realised within the NMSSM [113,114,127,175,[192][193][194][195][196][197][198][199].…”
Section: Lep and E + E − Collidersmentioning
confidence: 99%
See 1 more Smart Citation
“…3. Clearly, even very light CP-even scalars are not ruled out if ξ 1 is sufficiently small, and such scenarios can indeed be realised within the NMSSM [113,114,127,175,[192][193][194][195][196][197][198][199].…”
Section: Lep and E + E − Collidersmentioning
confidence: 99%
“…Early studies [113,127,[193][194][195][196] confined themselves to the standard Higgs search channels…”
Section: Lep and E + E − Collidersmentioning
confidence: 99%
“…Also if hints for such an extended Higgs sector are observed at the LHC, only a LC will be able to study its properties in more detail. Earlier studies of the detection of NMSSM Higgs bosons at e + e − colliders can be found in [428][429][430][431][432][433].…”
Section: The Higgs Portal 21mentioning
confidence: 99%
“…1b. The discovery limits in the model are about 50 fb for m S = 80 GeV and 30 fb for m S = 40 GeV at a luminosity of 500 pb −1 for √ s = 175 GeV and at one of 300 pb −1 for √ s = 192 and 205 GeV [12]. We cannot impose any experimental constraints on tan β at √ s = 175 GeV.…”
Section: The Neutral Higgs Sectormentioning
confidence: 95%